Steady state visual evoked potentials in schizophrenia: A review - Schielke, Alexander; Krekelberg, Bart (Frontiers in Neuroscience, 2022)
Over the past decades, researchers have explored altered rhythmic responses to visual stimulation in people with schizophrenia using steady state visual evoked potentials (SSVEPs). Here we systematically review studies performed between 1954 and 2021, as identified on PubMed. We included studies if they included people with schizophrenia, a control group, reported SSVEPs as their primary outcome, and used quantitative analyses in the frequency domain. We excluded studies that used SSVEPs to primarily quantify cognitive processes (e.g., attention). Fifteen studies met these criteria. These studies reported decreased SSVEPs across a range of frequencies and electrode locations in people living with schizophrenia compared to controls; none reported increases. Null results, however, were common. Given the typically modest number of subjects in these studies, this is consistent with a moderate effect size. It is notable that most studies targeted frequencies that fall within the alpha and beta band, and investigations of frequencies in the gamma band have been rare. We group test frequencies in frequency bands and summarize the results in topographic plots. From the wide range of approaches in these studies, we distill suggested experimental designs and analysis choices for future experiments. This will increase the value of SSVEP studies, improve our understanding of the mechanisms that result in altered rhythmic responses to visual stimulation in schizophrenia, and potentially further the development of diagnostic tools.